Stat3 promotes mitochondrial transcription and oxidative respiration during maintenance and induction of naive pluripotency. (22nd February 2016) - Carbognin, Elena; Betto, Riccardo M; Soriano, Maria E; Smith, Austin G; Martello, Graziano
Abstract: Transcription factor Stat3 directs self‐renewal of pluripotent mouse embryonic stem (ES) cells downstream of the cytokine leukemia inhibitory factor (LIF). Stat3 upregulates pivotal transcription factors in the ES cell gene regulatory network to sustain naïve identity. Stat3 also contributes to the rapid proliferation of ES cells. Here, we show that Stat3 increases the expression of mitochondrial‐encoded transcripts and enhances oxidative metabolism. Chromatin immunoprecipitation reveals that Stat3 binds to the mitochondrial genome, consistent with direct transcriptional regulation. An engineered form of Stat3 that localizes predominantly to mitochondria is sufficient to support enhanced proliferation of ES cells, but not to maintain their undifferentiated phenotype. Furthermore, during reprogramming from primed to naïve states of pluripotency, Stat3 similarly upregulates mitochondrial transcripts and facilitates metabolic resetting. These findings suggest that the potent stimulation of naïve pluripotency by LIF/Stat3 is attributable to parallel and synergistic induction of both mitochondrial respiration and nuclear transcription factors. Synopsis: The LIF/STAT3 pathway promotes naïve pluripotency and proliferation in embryonic stem cells. To do this, in addition to its nuclear role, STAT3 translocates to the mitochondrion, regulates mitochondrial transcription and enhances mitochondrial respiration. The LIF/Stat3 axis promotes mitochondrial gene expression and respiration in ES cells. Mitochondrial respiration determines optimal ES cell proliferation. LIF‐dependent up‐regulation of mitochondrial activity contributes to induction of naïve pluripotency. Abstract : The LIF/STAT3 pathway promotes naïve pluripotency and proliferation in embryonic stem cells. To do this, in addition to its nuclear role, STAT3 translocates to the mitochondrion, regulates mitochondrial transcription and enhances mitochondrial respiration.